THE ROLE OF GAS PURIFICATION METHODS IN THE CHEMICAL INDUSTRY (International journal of artificial intelligence, 2026)
Gas purification is one of the important processes in industry, energy, chemical production, and environmental protection. Gases released into the atmosphere may contain dust, toxic substances, harmful chemical compounds, and various aerosols. These harmful components negatively affect human health, flora and fauna, and the overall condition of the environment. Therefore, the development and practical application of gas purification technologies play a significant role in reducing environmental problems. In this article, we will provide information about some methods of gas purification.